A ética das relações: percepção de médicos e enfermeiros sobre os conflitos na prática profissional - Pimentel, Déborah Mônica Machado (2013)
A cross-sectional study, qualitative, descriptive, willing to know, from the perception of physicians and nurses, the ethical relations in professional practice and identify ethical conflicts among health professionals and patients, and colleagues in the field. To achieve the objectives, a systematic review of the literature a study was conducted on 515 articles from the period 2004-2011 with methodology driven by Cochrane Handbook Publications. The simple and casual sample of field research was composed of nurses and doctors of health institutions in Aracaju city. It was used a collection instrument with the following variables: job profile, working conditions, ethical conflicts, contribution of ethical education at the undergraduate level for dealing with conflicts. The survey was complited by inviting professionals to participate in focus groups with sessions of two hours duration, with flexible script about favorable and unfavorable conditions to the maintenance of ethical relationships at work and ethics training to face the conflict. The categorical analysis technique was utilized to evaluate data. The results of the survey revealed that, from the point of view of professionals, ethics training does not meet the requirements of professional practice. As a solution, improving the disciplines of communication skills and medical humanities, a better preparation of teachers and the teaching of technical and scientific expertise are linked to ethical aspects, were suggestions discussed in all academic disciplines. Focus groups concluded that health professionals are more concerned with the diseases than patients in practice dehumanized. Lack of communication skills, coupled with neglect of interpersonal and interprofessional relationships, poor working conditions, conflicts of interest and favor relationship conflicts, promoting errors, complaints, discomfort, discredit to professionals and harm to patients. The professionals themselves have recognized the need to be more supervised and punished. The focus groups revealed ethical conflicts in interpersonal relationships more serious than those presented in the literature, demonstrating great pain, with relevant moral anguish. Both categories showed professional training as insufficient and responsible for the conflict, by not prioritizing ethics or the basic principles of bioethics.